Active Learning by Design: An Undergraduate Introductory Public Health Course - Karin eYeatts (Frontiers Media S.A., 2014)
Principles of active learning were used to design and implement an introductory public health course. Students were introduced to the breadth and practice of public health through team and individual-based activities. Team assignments covered topics in epidemiology, biostatistics, health behavior, nutrition, maternal and child health, environment, and health policy. Students developed an appreciation of the population perspective through an experience trip and related intervention project in a public health area of their choice. Students experienced several key critical component elements of a public health undergraduate major; they cover key public health domains, experience public health practice, and integrated concepts with their assignments. In this paper, course assignments, lessons learned, and student successes are described. Given the increased growth in the undergraduate public health major, these active learning assignments may be of interest to undergraduate public health programs at both liberal arts colleges and research universities.